Cognitive deficits in progressive supranuclear palsy on the Repeatable Battery for the Assessment of Neuropsychological Status. Issue 5 (28th May 2019) - Duff, Kevin; McDermott, Dana; Luong, Dan; Randolph, Christopher; Boxer, Adam L.
ABSTRACT: Progressive supranuclear palsy (PSP) is associated with a variety of cognitive deficits, as well as motor and psychiatric disturbances. As clinical trials for PSP evolve, briefer screening instruments will be needed to determine cognitive effects of interventions. The Repeatable Battery for the Assessment of Neuropsychological Status (RBANS) may fill this gap. Three hundred four participants diagnosed with Richardson's syndrome of PSP were evaluated with the RBANS, as well as other scales typically used in PSP. RBANS performances for these participants fell significantly below expectations for the Total Scale score and all five Indexes. Cognitive scores on the RBANS were also significantly related to other markers of PSP (e.g., motor and functional abilities, depression, global cognition). Compared to other clinical conditions from the literature, patients with PSP show impairment on tests of visuospatial perception and construction and attention. Although additional research is needed, the current study supports the clinical applicability of the RBANS in patients with PSP, as well as its potential for future clinical trials.